IMPLEMENTASI STANDAR PENDIDIKAN ISLAM NON FORMAL MDT (MADRASAH DINIYAH TAKMILIYAH) DI INDONESIA - A. Natsir Fitriono (AR ROSYAD: Jurnal Keislaman dan Sosial Humaniora, 2022)
MDT education Model in Indonesia today in reality that the existence of Madrasah Diniyah Takmiliyah not dimasifkan quantity. The problem is whether the community is interested in sending (learning) to MDT? From the background of the above problems, the researchers want to analyze about: (1) How the implementation of non formal Islamic education standards MDT in Indonesia. (2) What obstacles are faced, and how the solution.Research methods are descriptive analytical, where research sources obtained through the study of literature. The results prove that the implementation of non formal Islamic education standards MDT in Indonesia there are several obstacles in its implementation include: (1) funding. (2) The Power of teaching. (3) facilities and facilities, as well as. (4) Time / Lesson Hours. So it takes a solution or effective steps in optimizing Madrasah Diniyah Takmiliyah in Indonesia. The solution is: (a) the need to improve the quality of academic by equipping students with the ability to religion properly and correctly. (b) the need to install human resources by selecting qualified teachers and optimal management. (c) maximization of the role, in addition to the collection of funds as a quality controller Madrasah Diniyah, also needed donors or donors who participated in helping in terms of funding. (d) the need to increase the role of parents, and local communities as objects as well as subjects of Education.